Belief in equality of opportunities and attitudes towards immigrants in Italy: The mediator effect of institutional trust - Capoccia, Debora (2020)
The thematic area of the research is the populist narrative in Italy and the analysis of the phenomenon through the perception of equality of opportunities, the trust on institutions and the attitudes towards immigrants. In Italy with the growing of national populism there have been witnessed some intolerant attitudes towards immigrants. The differences between majority group and minority group and a discriminating narrative have been observed among the population. We therefore wanted to research the influences and the connections among these constructs. Based on literature review, we found that the relation between equality of opportunities and attitudes towards immigrants has not been deeply studied. The data used in the study are part of the database of European Social Survey (ESS) Round 9. The study includes the analysis of the responses given by two thousand, seven hundred forty-five Italian people to the constructs that constituted the objects of the research. The results showed positive and significant correlations among equality of opportunities beliefs, attitudes towards immigrants and trust in institutions. A simple mediation model was tested and revealed an indirect effect of equality of opportunities beliefs and attitudes towards immigrants through trust in institutions. The implications of the results for the improvements of intergroup contact are discussed.